2004
DOI: 10.1007/s10311-004-0062-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of hydrophobic organic contaminants and quality of organic carbon

Abstract: U.S. laws require that contaminant bioaccumulation potential be evaluated before dredged material can be recycled. Simple fugacity models, e.g. organic contaminant aqueous partition coefficient (K oc )-derived theoretical bioaccumulation potential, are commonly used to estimate the partitioning of hydrophobic organic contaminants between sediment organic matter and organism lipid. K oc -derived models, with or without the addition of a soot carbon term, did not accurately or consistently predict total polycycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Maximum exchangeable concentrations of metals were 20 mg/kg of arsenic, 5 mg/kg of cadmium, 60 mg/kg of chromium, 10 to 80 mg/kg of copper, 1 mg/kg of mercury, and 10 to 50 mg/kg of nickel (for lead and zinc, see Table 1). The amounts (mean Ϯ standard deviation) of organic carbon were high in most sediments (TOC, 23% Ϯ 11%; OC, 27% Ϯ 13%; BC, 7.6% Ϯ 2.9%) but were of similar magnitude to those measured for other industrialized harbor sediments [11,14,15]. Pore-water ammonia and sulfide concentrations were less than 50 g/L except in sediment 38, for which the concentration of ammonia was 350 g/L.…”
Section: Test Sediment Properties and Contaminant Concentrationsmentioning
confidence: 52%
See 2 more Smart Citations
“…Maximum exchangeable concentrations of metals were 20 mg/kg of arsenic, 5 mg/kg of cadmium, 60 mg/kg of chromium, 10 to 80 mg/kg of copper, 1 mg/kg of mercury, and 10 to 50 mg/kg of nickel (for lead and zinc, see Table 1). The amounts (mean Ϯ standard deviation) of organic carbon were high in most sediments (TOC, 23% Ϯ 11%; OC, 27% Ϯ 13%; BC, 7.6% Ϯ 2.9%) but were of similar magnitude to those measured for other industrialized harbor sediments [11,14,15]. Pore-water ammonia and sulfide concentrations were less than 50 g/L except in sediment 38, for which the concentration of ammonia was 350 g/L.…”
Section: Test Sediment Properties and Contaminant Concentrationsmentioning
confidence: 52%
“…A molar excess of AVS over SEM (sum of cadmium, copper, nickel, mercury, lead, and zinc) was observed for all sediments that had high metal concentrations (e.g., AVS Ϫ SEM ϭ 10-120 mol/g). Most previous studies have found that OC determined by LOI overestimates TOC [11,14], and TOC, rather than OC, measurements were used to normalize hydrocarbon concentrations for comparison with SQGs [16]. The pH of the sediments ranged from 6.5 to 7.9.…”
Section: Test Sediment Properties and Contaminant Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were again removed and allowed to cool to room temperature before being weighed for the second time to ensure that all combustible matter had been removed. The loss-on-ignition temperature of 375°C is sufficient to oxidize the easily ignitable organic carbon (Fredrickson et al 2004) and is more reproducible than results at 550°C, which in addition to easily ignitable organic carbon also oxidizes any black carbon (Accardi-Dey and Gschwend 2003) and often overestimates the amount of organic matter (Smedes and Nummerdor 2003). The loss-on-ignition (LOI) organic matter masses were then calculated and recorded based on the following formula:…”
Section: Soil Texturementioning
confidence: 99%
“…[15][16][17] DOM also plays a crucial role in defining the water solubility and bioavailability of toxic metal species and complexes, and of organic pollutants. [18][19][20][21][22][23][24] These considerations account for the importance of characterising lakewater for nitrate and DOM among other parameters, and of extending the studies to a wide number of lacustrine systems. As far as the second point is concerned, an important limit to lakewater characterisation is represented by the (moderate but non negligible) instrumentation requirements that may be problematic for small laboratories.…”
Section: Introductionmentioning
confidence: 99%